FFLO order in ultra-cold atoms in three-dimensional optical lattices. (18th May 2015) - Rosenberg, Peter; Chiesa, Simone; Zhang, Shiwei
Abstract: We investigate different ground-state phases of attractive spin-imbalanced populations of fermions in three-dimensional optical lattices. Detailed numerical calculations are performed using Hartree–Fock–Bogoliubov theory to determine the ground-state properties systematically for different values of density, spin polarization and interaction strength. We first consider the high density and low polarization regime, in which the effect of the optical lattice is most evident. We then proceed to the low density and high polarization regime where the effects of the underlying lattice are less significant and the system begins to resemble a continuum Fermi gas. We explore the effects of density, polarization and interaction on the character of the phases in each regime and highlight the qualitative differences between the two regimes. In the high-density regime, the order is found to be of Larkin–Ovchinnikov type, linearly oriented with one characteristic wave vector but varying in its direction with the parameters. At lower densities the order parameter develops more structures involving multiple wave vectors.